RNA sequencing reveals a transcriptomic portrait of human mesenchymal stem cells from bone marrow, adipose tissue, and palatine tonsils. Issue 1 (December 2017) - Cho, Kyung-Ah; Park, Minhwa; Kim, Yu-Hee; Woo, So-Youn; Ryu, Kyung-Ha
Abstract Human mesenchymal stem cells (MSCs) are adult multipotent cells that have plasticity and inhabit the stroma of diverse tissues. The potential utility of MSCs has been heavily investigated in the fields of regenerative medicine and cell therapy. However, MSCs represent diverse populations that may depend on the tissue of origin. Thus, the ability to identify specific MSC populations has remained difficult. Using RNA sequencing, we analyzed the whole transcriptomes of bone marrow-derived MSCs (BMs), adipose tissue-derived MSCs (AMs), and tonsil-derived MSCs (TMs). We categorized highly regulated genes from these MSC groups according to functional gene ontology (GO) classification. AMs and TMs showed higher expression of genes encoding proteins that function in protein binding, growth factor, or cytokine activity in extracellular compartments than BMs. Interestingly, TM were highly enriched for genes coding extracellular, protein-binding proteins compared with AMs. Functional Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis also showed differentially enriched signaling pathways between the three MSC groups. Further, we confirmed surface antigens expressed in common and in a tissue-specific manner on BMs, AMs, and TMs by flow cytometry analysis. This study provides comprehensive characteristics of MSCs derived from different tissues to better understand their cellular and molecular biology.